Cementum analysis in cleidocranial dysostosis - Manjunath K; Kavitha B; Saraswathi T; Sivapathasundharam B; Manikandhan R (Wolters Kluwer Medknow Publications, 2008)
Objective: Cleidocranial dysostosis (CCD) is a skeletal disorder associated with dental anomalies such as failure or delayed eruption of permanent teeth and multiple impacted supernumerary or permanent teeth. Absence of cellular cementum at the root apex is presumed to be one of the factors for failure or delayed eruption. The aim of this study was to analyze the root cementum of supernumerary(S) and permanent teeth (P) of a CCD patient and to compare the findings with those of normal individuals with special emphasis on delayed eruption. Materials and Methods: Ground sections of 12 extracted teeth (9S + 3P) of a CCD patient and 12 teeth of normal individuals (5S + 7P) were taken for the study. The sections were longitudinal and 50 µm thick. Root characteristics were recorded with the aid of a light microscope. Results: The absence of apical cellular cementum, increased root resorption and increased percentage of the gap type of cemento-enamel (C-E) junctions were significant findings noted both in the supernumerary and permanent teeth of the CCD patient. Conclusion: The presumption of cellular cementum is essential for tooth eruption is not supported by the findings of the present study. Delayed exception could be attributed to various other factors like mechanical obstruction, reduced serum alkaline phosphatase levels etc. Also, the significance of the increased percentage of the gap type of C-E junctions and its role in tooth eruption has to be further evaluated.